Primary thyroid lymphoma: A single-center experience - Lee, Jin Seok; Shin, Su-Jin; Yun, Hyeok Jun; Kim, Seok Mo; Chang, Hojin; Lee, Yong Sang; Chang, Hang-Seok (Frontiers in Endocrinology, 2023)
Background: Primary thyroid lymphoma (PTL) is a very rare entity accounting for 5% of all thyroid malignancies and less than 2% of lymphomas. PTLs are classified as non-Hodgkin’s B-cell lymphomas in the majority of cases, although Hodgkin’s lymphoma of the thyroid has also been identified. This study aimed to identify the clinical, biochemical, and pathological features of primary thyroid lymphomas. Methods: From January 2008 to December 2020, data from patients diagnosed with PTL treated at the Gangnam Severance Hospital, including clinical, biochemical, and pathological features of thyroid lymphomas, were assessed. Results: Of 10 patients, nine women and one man, with a median age of 62 (range, 44–82) years were included. Fine needle aspiration biopsy was performed in nine patients and surgical resection was performed in one patient without biopsy. Excisional and surgical biopsies were performed in all patients, including five who underwent excisional biopsy and five who underwent thyroidectomy. Histological analyses revealed that all 10 lymphomas were non-Hodgkin B-cell lymphoma; six patients had diffuse large B-cell lymphoma, three had mucosa-associated lymphoid tissue lymphoma, and one had Burkitt lymphoma. Four patients received chemotherapy, two were treated with chemoradiation therapy, one received radiation therapy only, one did not require more treatment after surgery, one refused treatment, and one was transferred to another hospital. Conclusions: Although PTLs are scarce, clinicians should be aware of this rare entity and evaluate and treat PTLs on an individual basis.